The addition of heat pump electricity load profiles to GB electricity demand: Evidence from a heat pump field trial. (15th October 2017) - Love, Jenny; Smith, Andrew Z.P.; Watson, Stephen; Oikonomou, Eleni; Summerfield, Alex; Gleeson, Colin; Biddulph, Phillip; Chiu, Lai Fong; Wingfield, Jez; Martin, Chris; Stone, Andy; Lowe, Robert
Highlights: An aggregated load profile is constructed using data from 696 heat pumps in GB. It contains a morning and evening peak, falling to 40% of its peak value overnight. After diversity maximum demand is calculated as 1.7 kWe per heat pump. A first order approximation of the impact of 20% uptake of heat pumps is presented. This is shown to lead to the GB national grid evening peak increasing by 14%. Abstract: Previous studies on the effect of mass uptake of heat pumps on the capability of local or national electricity grids have relied on modelling or small datasets to create the aggregated heat pump load profile. This article uses the UK Renewable Heat Premium Payment dataset, which records the electricity consumption of nearly 700 domestic heat pump installations every 2 minutes, to create an aggregated load profile using an order of magnitude more sites than previously available. The aggregated profile is presented on cold and medium winter weekdays and weekends and is shown to contain two peaks per day, dropping overnight to around 40% of its peak. After Diversity Maximum Demand (ADMD) for the population of heat pumps is calculated as 1.7 kW per site; this occurs in the morning, whereas the peak national grid demand occurs in the evening. Analysis is carried out on how heat pump ADMD varies with number of heat pumps in the sample. A simple upscaling exercise is presented to give a first order approximation of the increase in GB peak electricity demand with mass deployment of heat pumps. It is found that peak grid demand increases by 7.5 GW (14%) with 20% of households using heat pumps. The effect of the same heat pump uptake on grid ramp rate is also discussed; this effect is found to be minor. Finally, a comparison of heat pump and gas boiler operation is given, discussing day and night time operation and mean and peak power at different external temperatures.